Regulation of thymic T regulatory cell differentiation by TECs in health and disease. (5th August 2021) - Tao, Zehua; Jiang, Yalan; Xia, Sheng
Abstract: The thymus produces self‐limiting and self‐tolerant T cells through the interaction between thymocytes and thymus epithelial cells (TECs), thereby generating central immune tolerance. The TECs are composed of cortical and medullary thymic epithelial cells, which regulate the positive and negative selection of T cells, respectively. During the process of negative selection, thymocytes with self‐reactive ability are deleted or differentiated into regulatory T cells (Tregs). Tregs are a subset of suppressor T cells that are important for maintaining immune homeostasis. The differentiation and development of Tregs depend on the development of TECs and other underlying molecular mechanisms. Tregs regulated by thymic epithelial cells are closely related to human health and are significant in autoimmune diseases, thymoma and pregnancy. In this review, we summarize the current molecular and transcriptional regulatory mechanisms by which TECs affect the development and function of thymic Tregs. We also review the pathophysiological models of thymic epithelial cells regulating thymic Tregs in human diseases and specific physiological conditions.